Overview of colorectal resections in a reference center in Curitiba – Brazil: Experience with open and laparoscopic approach - Domingos, Micheli Fortunato; Pinho, Renato Valmassoni; Coelho, Júlio Cezar Uili; Ferronatto, Guilherme Figueiró; Savio, Mariane Christina; Blum, Caroline; Weiss, Andre Gubert; Aguilera, Yan Sacha Hass (Journal of Coloproctology, 2018)
Introduction Minimally invasive approach has become the preferential option for the treatment of surgical diseases of the Gastrointestinal Tract, due to its numerous advantages. However, in the Colorectal Surgery field, the acceptance of videolaparoscopy was slower. For example, an American study showed that the percentage of laparoscopic cholecystectomy increased from 2.5% in 1988 to 73.7% in 1992, the rate of laparoscopic sigmoidectomy increased from 4.3% in 2000 to only 7.6% in 2004.Objecties Our goal was to compare several variables between patients submitted to colorectal resections performed through open surgery or videolaparoscopy.Methods This is a retrospective observational study performed in a Teaching Private Hospital of the City of Curitiba, Brazil, with the revision of 395 medical charts of patients subjected to colorectal resections from January 2011 through June 2016.Results 349 patients were included in the study. 243 (69.6%) were subjected to laparoscopic colon resection (LCR) and 106 (30.4%) to open colon resection (OCR). Mean age was 62.2 years for patients undergoing LCR and 68.8 year for OCR (p = 0.0082). Among emergency procedures, 92.5% consisted of OCR and 7.5% were LCRs. Surgery duration was similar in both types of access (196 min in OCR versus 195 min in LCR; p = 0.9864). Diet introduction was earlier in laparoscopic surgery and anastomotic fistula rate was similar in both groups (OCR 7.5% and LCR 6.58%; p = 0.7438). Hospital stay was shorter in patients undergoing laparoscopic resections (7.53 ± 7.3 days) than in the ones undergoing open surgery (17.2 ± 19.3) (p < 0.001). In the OCR group, 70 patients needed ICU admission (66%), and stayed a mean of 12.3 days under intensive care. In the LCR group, however, only 30 needed ICU (12.3%), and the ones who needed it stayed a mean of 5.6 days (p < 0.001).Conclusions Videolaparoscopic approach is a safe and effective option in the treatment of colorectal diseases. Surgery duration and anastomotic fistula rates are similar to the open resections. Hospital stay and ICU stay durations, however, were shorter in patients submitted to laparoscopic colectomies.
Keywords: Colectomy; Colorectal Surgery; Laparoscopic; Colon